Bokujinkai: Japanese calligraphy and the postwar avant-garde - Bogdanova-Kummer, Eugenia (Japanese visual culture, 2020)
The Bokujinkai-or 'People of the Ink'-was a group formed in Kyoto in 1952 by five calligraphers: Morita Shiryū, Inoue Yūichi, Eguchi Sōgen, Nakamura Bokushi, and Sekiya Yoshimichi. The avant-garde movement they launched aspired to raise calligraphy to the same level of international prominence as abstract painting. To this end, the Bokujinkai collaborated with artists from European Art Informel and American Abstract Expressionism, sharing exhibition spaces with them in New York, Paris, Tokyo, and beyond. The first English-language book to focus on the postwar history of Japanese calligraphy, Bokujinkai: Japanese Calligraphy and the Postwar Avant-Garde explains how the Bokujinkai rerouted the trajectory of global abstract art and attuned foreign audiences to calligraphic visualities and narratives.
Keywords: Hochschulschrift; Geschichte 1950-1965; Informel; Abstrakter Expressionismus; Europa; USA; Beziehung; Kalligrafie; Japan; Bokujinkai